Multitasking in the Era of Constant Connectivity: A Cognitive Analysis of Its Costs on Mental Performance and Well-Being - Subardjo, Ratna Yunita Setiyani; Khan, Zeeshan (The Indonesian Institute of Science and Technology Research, 2025)
Multitasking is becoming a crucial part of everyday life for knowledge workers, students, and anybody navigating technologically advanced environments in the digital age. Emerging empirical research shows that digital multitasking imposes significant cognitive and psychological demands, despite being frequently seen as an indication of efficiency. The effects of digital multitasking on mental health, productivity, and cognitive load are examined critically in this article. We contend, based on theoretical frameworks and empirical data, that the apparent increases in productivity are mostly a mirage, masking significant reductions in working memory, attention span, and emotional control. This research provides a thorough examination of the trade-offs related to continuous task-switching in the digital setting by utilizing a conceptual framework that connects digital multitasking with cognitive and psychological effects. Current research is compiled to show the wider repercussions on personal health and productivity at work, highlighting the necessity of evidence-based tactics to lessen the negative consequences of multitasking in today's digital world.